(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article describes the formation and development of cultural-economic centers and micro-oases on the borders of the right and left banks of Amudarya. The article describes the formation and development of cultural-economic centers and micro-oases on the borders of the right and left banks of Amudarya.